A MATHEMATICAL MODEL FOR WASTEWATER TREATMENT PROCESS OF AN OXIDATION POND (Jurnal Teknologi (Sciences & Engineering), 2016)
This study presents a mathematical model for wastewater treatment process (WWTP) of an oxidation pond. The model permits investigating the effects of a biological-based product called mPHO on the degradation of contaminants as well as increase the amount of dissolved oxygen (DO) in the pond. At this aim, an ordinary differential equation with coupled equations has been developed to study the correlation between the amount of bacteria (phototrophic and Coliform), chemical oxygen demand (COD), and dissolved oxygen (DO) existing in the pond. The mathematical model is employed to simulate the behaviour of the system where the numerical results demonstrate that the proposed model gives a good approximation of the interaction processes that occur naturally between biological and chemical substances involved in the pond